Expanding human-based predictive models capabilities using organs-on-chip: A standardized framework to transfer and co-culture human iPSCs into microfluidic devices - Rontard, Jessica; Maisonneuve, Benoît GC; Honegger, Thibault (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
There is an urgent need for predictive preclinical models to enhance the success rate of clinical trial outcomes. One of the main reasons for drug attrition is the lack of translational models, methods using human cells are particularly in the spotlight of regulatory bodies as they offer an alternative to in vivo studies and have the potential to improve the translational of preclinical trials. Organs-on-Chips (OoCs) are sensible candidates to reduce the cost and the ethical burden of animal models while accelerating and de-risking drug development. The innovation of such systems is based on both the increased relevance of the cells used and the ability to build precise, yet physiologically relevant, complex architectures. The use of microfluidic technologies with human induced pluripotent stem cells (hiPSCs) opens new routes to create relevant in vitro approaches as they will soon be able to reproduce clinical characteristics of donors or specific populations. The adoption of OoC models by pharmaceutical industries, and in fine by regulatory agencies, still requires: (i) establishing standardized, reproducible, robust, and replicable cell culture protocols with specific validation and characterization criteria, (ii) evidence that the technology predicts human responses, thus allowing to contribute efficiently and reliably to clinical trials success of novel therapeutics, and (iii) evidence that the models refine and reduce animal testing without compromising with the quality and the pertinence of the data generated.